Ethical Leadership and Governance Quality: Exploring Public Trust and Citizen Participation in Cambodian District Administration - Sarom Mok; Sereyrath Em (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study: This study aimed to develop an ethical leadership model for Cambodian district administration and to determine how ethical leadership characteristics inspire and sustain good governance, particularly in relation to honesty, concern for citizens, participation, accountability, transparency, the rule of law, and administrative competence. Methodology: A qualitative case study design was used. Purposive sampling was used to select 25 district administration officials (≥5 years’ service). Data were collected through face-to-face, open-ended interviews (audio-recorded using a digital audio cassette recorder) and document review. The interview guide was adapted from the Ethical Leadership Scale. Khmer transcripts were thematically analyzed using constant comparison and two-cycle coding. Main Findings: Key themes were honesty, concern for people, ethics infrastructure, ethics training, citizen participation, access to information, transparency, accountability, rule of law, competency, and autonomy. Most participants perceived leaders as dishonest (88%) and unconcerned with public interest (80%). All participants emphasized ethics infrastructure, information access, transparency, accountability, and the rule of law (100%). Competency was viewed positively (88%). Ethics training (32%) and autonomy (16%) appeared less frequently but were still identified as important enabling factors. Novelty/Originality of this study: This study contributes to social science literature by examining ethical leadership as a social mechanism that shapes citizen trust, participation, institutional legitimacy, and governance quality within Cambodian district administration. By integrating leadership theory, governance theory, and social trust perspectives, the study provides a contextual understanding of how ethical leadership influences state–society relationships in a developing-country setting.